Taxogenomic and Comparative Genomic Analysis of the Genus Saccharomonospora Focused on the Identification of Biosynthetic Clusters PKS and NRPS - Ramírez-Durán, Ninfa; de la Haba, Rafael R.; Vera-Gargallo, Blanca; Sánchez-Porro, Cristina; Alonso-Carmona, Scarlett; Sandoval-Trujillo, Horacio; Ventosa, Antonio (Frontiers in Microbiology, 2021)
Actinobacteria are prokaryotes with a large biotechnological interest due to their ability to produce secondary metabolites, based on the presence on their genomes of two main biosynthetic gene clusters (BGCs): polyketide synthase (PKS) and non-ribosomal peptide synthase (NRPS). Most studies on bioactive products have been carried out on actinobacteria isolated from soil, freshwater or marine habitats, while very few have been focused on halophilic actinobacteria isolated from extreme environments. In this study we have carried out a comparative genomic analysis of the actinobacterial genus Saccharomonospora, which includes species isolated from soils, lake sediments, marine or hypersaline habitats. A total of 19 genome sequences of members of Saccharomonospora were retrieved and analyzed. We compared the 16S rRNA gene-based phylogeny of this genus with evolutionary relationships inferred using a phylogenomic approach obtaining almost identical topologies between both strategies. This method allowed to unequivocally assign strains into species and to identify some taxonomic relationships that need to be revised. Our study supports a recent speciation event occurring in Saccharomonospora halophila and Saccharomonospora iraqiensis. Concerning the identification of BGCs, a total of 18 different types of BGCs were detected in the analyzed genomes of Saccharomonospora, including PKS, NRPS and hybrid clusters which might be able to synthetize 40 different putative products. In comparison to other genera of the Actinobacteria, members of the genus Saccharomonospora showed a high degree of novelty and diversity of BGCs.